Vehicle Detection and Counting Using Adaptive Background Model Based on Approximate Median Filter and Triangulation Threshold Techniques - El-Khoreby M.A.; Abu-Bakar S.A.R.; Mokji M.M.; Omar S.N. (Pleiades Publishing, 2024)
Indexed by WOS/SCOPUS/ERA